2023
DOI: 10.3390/su15119137
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Potato Peels for Bioethanol Production through Various Pretreatment Strategies and an In-House-Produced Multi-Enzyme System

Abstract: This study aimed to explore the viability of converting potato peel waste into bioethanol using a custom-produced multi-enzyme preparation. Various pretreatment approaches were employed on the potato peels, including thermal, chemical, and thermo-chemical methods. These methods involved boiling for 30 and 60 min, steaming at different pressures and durations, and applying different concentrations of chemicals, including H2SO4, HNO3, CH3COOH, HCl, NaOH, Ca(OH)2, KOH, NH3, and H2O2, either individually or in com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
0
0
0
Order By: Relevance
“…The thermochemical treatment proved more effective in the monomerization of polymeric sugars of PPW. Several studies have indicated higher yields of useful compounds from the alkali and alkali-plus-steam treatment of PPW [47,[49][50][51][52]. The linear and the quadratic effects of the variables studied and their interaction on the response yield was observed using analyses of variance (ANOVA).…”
Section: Rsm Optimization and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermochemical treatment proved more effective in the monomerization of polymeric sugars of PPW. Several studies have indicated higher yields of useful compounds from the alkali and alkali-plus-steam treatment of PPW [47,[49][50][51][52]. The linear and the quadratic effects of the variables studied and their interaction on the response yield was observed using analyses of variance (ANOVA).…”
Section: Rsm Optimization and Validationmentioning
confidence: 99%
“…However, other means to improve the saccharification efficiencies of the procedures reported here, such as varying steam pressures, might be employed to increase the yields. Soni et al [47] have explored various conditions by using different alkali and acid concentrations to treat PPW and assessing their potential to produce bioethanol. They reported 368.53 mg/g of RS after 72 h using alkali-treated PPW, and after enzymatic hydrolysis ethanol concentration was recorded as 19.9g/L.…”
Section: Introductionmentioning
confidence: 99%